Sistem Informasi Penggajian Berbasis Excel pada Too XYZ - Putri, Wikeu Asmara; Anwar, Sifaul (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2025)
ABSTRACT This research aims to analyze the existing payroll information system at XYZ, design a new system, implement it, and conduct testing. XYZ, a growing building materials retailer, employs a large number of staff. The current payroll process, which involves manual data entry for each payroll cycle, lacks automation, creating potential risks and inefficiencies. The research employs a descriptive approach, utilizing the PIECES system analysis method and the Waterfall development model. The author also conducted a literature review, drawing from relevant books and online sources. The final phase involves system testing using Black-box testing, confirming that the developed application aligns with the initial design and meets the required functions, including accurate data processing, recording, and calculation. This system is expected to enhance operational efficiency at XYZ.